(3RHOI GdCMcGe aj GNJdGa ePGgH GdCFeI GdCQHYIs - (3GdZRfhj, YeQ Hf ESMGb Hf CMeO, J (B773 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; QH cd YHO hGdMeO ddg hdj GdMeO bO bGd CHh MaU QMeg Gddg gPG cJGH aj GdNdGajGJ CHhGHg Ydi GdfXGe YTQIs
(3BNQgG (B:s
(3cJGH GdhUGjG hHYO fUa GdMhd eP MHdJ cMG dG Sbi GdehJ ajeG aYdJ heG CLGOj GdhGQK HGdeQVG de jedchG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 42s
(3eYLe GdeDdajf (B2 / 554s
(3cTa GdXfhf (B2 / 950s
(3TPQGJ GdPgH (B6 / 228s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs